2015
DOI: 10.1038/jcbfm.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neutrophils in Ischemic Stroke: Translational Insights from Experimental Studies

Abstract: Neutrophils have key roles in ischemic brain injury, thrombosis, and atherosclerosis. As such, neutrophils are of great interest as targets to treat and prevent ischemic stroke. After stroke, neutrophils respond rapidly promoting blood-brain barrier disruption, cerebral edema, and brain injury. A surge of neutrophil-derived reactive oxygen species, proteases, and cytokines are released as neutrophils interact with cerebral endothelium. Neutrophils also are linked to the major processes that cause ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
451
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 479 publications
(463 citation statements)
references
References 155 publications
8
451
0
4
Order By: Relevance
“…Because neutrophils are recruited at sites of cerebral ischemia and are important sources of proteases and reactive oxygen species capable of damaging the BBB, they have been previously incriminated as possible culprits contributing to BBB disruption and HT. 14,21 Furthermore, in recent years, neutrophil to lymphocyte ratio has emerged as a predictor of short-and long-term outcomes in ischemic stroke patients and of risk of HT in stroke patients treated with intravenous thrombolysis. 22 In line with this clinical data, we found that HG rats had an increase in neutrophil to lymphocyte ratio compared with NG rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because neutrophils are recruited at sites of cerebral ischemia and are important sources of proteases and reactive oxygen species capable of damaging the BBB, they have been previously incriminated as possible culprits contributing to BBB disruption and HT. 14,21 Furthermore, in recent years, neutrophil to lymphocyte ratio has emerged as a predictor of short-and long-term outcomes in ischemic stroke patients and of risk of HT in stroke patients treated with intravenous thrombolysis. 22 In line with this clinical data, we found that HG rats had an increase in neutrophil to lymphocyte ratio compared with NG rats.…”
Section: Discussionmentioning
confidence: 99%
“…13 Neutrophils are among the first circulating cells to respond to AIS and contribute to BBB disruption, brain edema, and HT. 14 Experimental studies revealed that hyperglycemia enhanced endothelial activation and neutrophil infiltration in the ischemic brain. 15,16 In addition, we have shown that neutrophils were central actors of proximal occlusion-induced downstream microvascular thromboinflammation (DMT), which participates to neurovascular damage in AIS.…”
mentioning
confidence: 99%
“…Although neutrophil phagocytic activity may help in removing necrotic cell debris and tissue healing, the destructive nature of neutrophils is causing collateral tissue destruction, disruption of the blood-brain barrier, and cerebral edema. 58 Neutrophils contribute to cerebral injury by releasing proteolytic enzymes and free radicals that have direct neurotoxic activity. In addition, intravascular accumulation of neutrophils impairs local blood flow leading to the no-reflow phenomenon of the affected microcirculation.…”
Section: Inflammatory Cellsmentioning
confidence: 99%
“…One explanation might be that a decrease in let7i permits a proliferation of neutrophils, a major source of plasma MMP9 post stroke. 1 However, let7i remained correlated with MMP9 when neutrophil count was adjusted for. Alternatively, MMP9 may have increased because of let7i regulation of genes that affect the production and release of MMP9.…”
Section: Neurology 87 November 22 2016mentioning
confidence: 95%
“…A range of damage-associated molecular patterns, cytokines, and chemokines are released to activate circulating leukocytes, vasculature, and brain cells. 1,2 This inflammatory response has an important role in acute ischemic stroke and can contribute to the final extent of brain damage. Improved understanding of the immune response in stroke and its regulation may afford novel opportunities to optimize recovery in ischemic stroke.…”
mentioning
confidence: 99%